Supporting Data for "Thermomechanical characterisation of polyamide 6 over a wide range of rates and temperatures" - Song, P; Trivedi, A; Hawkins, N; Graham, A; Chapman, D; Siviour, C (University of Oxford, 2024)
Supporting data and figures from the paper "Thermomechanical characterisation of polyamide 6 over a wide range of rates and temperatures" published in Polymer in 2024 by Song et al.